Salience, incentives, and timely compliance: Evidence from speeding tickets - Libor Dusek; Nicolas Pardo; Christian Traxler (Max Planck Institute for Research on Collective Goods, 2020)
This paper studies the enforcement of fines. We randomly assign 80,000 speeding tickets to treatments that increase the salience of the payment deadline, late penalties, or both. Stressing the penalties significantly and persistently increases payment rates. Emphasizing only the deadline is not effective. The findings from the RCT are consistent with a survey experiment which documents the treatments' impact on priors about parameters of the compliance problem. Exploiting discontinuous variation in fines, we then document a strong price responsiveness: a 1% increase in the payment obligation induces a 0.23 percentage point decrease in timely compliance. This semi-elasticity suggests that the impact of the salience nudges is equivalent to the effect of a 4-9% reduction in fines.
hdl:21.11116/0000-0006-629F-9
Keywords: K42; H26; D80; 330; Enforcement; fines; timely compliance; salience; nudges; deadlines; perceptions; RCT; RDD